Bumpless Transfer Control for Gas Turbine⁎This work is supported by the National Natural Science Foundation of China under Grant (61890920, 61890921, 61903059), in part by the Liaoning Provincial Education Department under Grant XLYC1808015, and Aviation Science Foundation of China under Grant 2019ZB063001. Issue 10 (2021) - Du, Jing-Wen; Sui, Yong-Feng; Wen, Si-Xin; Hao, Guang-Chao; Du, Xian; Sun, Xi-Ming
Abstract: This paper mainly studies a bumpless transfer controller which can be applied to a certain gas turbine. Due to the requirements of low exhaust emission and high combustion efficiency, the gas supply system of the gas turbine is composed of duty fuel, master fuel, and secondary fuel, which inevitably lead to the switching problem in the control system. In order to solve this problem, we have built a three-branch natural gas supply system in the Amesim software and established a gas turbine model in the Simulink software according to its mechanism. In addition, the gas turbine model and the natural gas system model are jointly simulated through the interface. Finally, in accordance with the traditional PID gas turbine controller, an active disturbance rejection controller (ADRC) is designed, which is combined with a bumpless transfer controller including differentiator and integrator to suppress the interference caused by fuel switching. The effectiveness and superiority of this strategy are verified by the complete joint simulations.